Crime and transition in central and eastern Europe - Završnik, Aleš; Šelih, Alenka (Springer New York, 2012)
Full-scale political change affects every level of a society, but perhaps nowhere as strikingly as in the areas of crime policy and law enforcement. Over the past two decades, the European nations that have moved from totalitarianism toward democracy have come to embody this trend, yet reliable sources on crime and law enforcement in these countries have not been readily accessible to the West.   Representing viewpoints seldom available to outsiders, the contributors to Crime and Transition in Central and Eastern Europe analyze changes in criminal activities and crime control strategies in the region, explain the political background underlying these developments, and assess their long-term social impact. Experts from Slovenia, Hungary, Croatia, Serbia, the Czech Republic, Poland, Bosnia and Herzegovina discuss the politicization of crime, the ongoing paradoxes regarding civil liberties, and the future of crime policy in comparative and country-specific terms. Among the topics featured in the book:   ·         Crime and crime control in transitional countries. ·         Politics, the media, and public perception of crime. ·         Surveillance: from national security to private industry. ·         Penal policy and political change. ·         Emerging trends: economic and organized crime, human trafficking, juvenile delinquency. ·         New perspectives on corruption in the region.   With this fascinating insight, Crime and Transition in Central and Eastern Europe is a singular reference for researchers and policymakers in criminology and political science, and historians with a special interest in European affairs and policy.